The Influence of Social Media Influencers on Purchase Intention of Local Personal Care Products - Feliciana Yovita Saputra; Wisnu Sakti Dewobroto (Research Collaboration Community (RCC), 2022)
Nowadays, Personal care products grow rapidly every year even in a red ocean industry. With changes in this digital era, personal care companies have to innovate in order to survive and grow. One of the ways is the use of digital marketing. There are many ways to do digital marketing and one of the popular methods is social media influencers. However, with so many new influencers on social media, marketers find it challenging to choose the right influencers to promote their products because not every influencer brings a significant impact. Choosing the wrong influencers could cause the business to lose money and harm the image of a product or a brand. On the other hand, choosing the right influencers may lead to the popularity of the product and an increase in sales. Based on that, this research is focusing on the influencers from the consumer’s point of view, in order to know the type of influencers that fit with the product offered. This research is based on literature study that describes Influencer credibility has a positive impact on consumers' purchase intention, attitude towards products, and advertising. Moreover, Influencer credibility could describe and evaluate an influencer based on their attractiveness, trustworthiness, and expertise.